The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.2460/ajvr.2000.61.559
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary protein and lipid on weight loss in obese ovariohysterectomized cats

Abstract: Cats can lose 25 to 30% of their obese body weight over 7 to 9 weeks without developing overt clinical signs of HL, provided that weight-reduction diets are highly palatable, contain a high quality protein, have a source of LCEFA, and are fortified with vitamins and microminerals. However, rapid weight loss may increase risk factors associated with development of diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
1
12
0
2
Order By: Relevance
“…In the current study, food-restricted glucose concentrations increased from week 0 to 24, suggesting decreased insulin sensitivity with weight gain; however, food-restricted blood insulin concentrations did not change over time. Szabo et al (2000) reported increased blood glucose concentrations in cats following ovariohysterectomy (and weight gain) with no increases in insulin concentration. Glucose concentrations reported by Szabo et al (2000) were similar to those measured in the current study.…”
Section: High-protein Diet Following Ovariohysterectomymentioning
confidence: 98%
See 1 more Smart Citation
“…In the current study, food-restricted glucose concentrations increased from week 0 to 24, suggesting decreased insulin sensitivity with weight gain; however, food-restricted blood insulin concentrations did not change over time. Szabo et al (2000) reported increased blood glucose concentrations in cats following ovariohysterectomy (and weight gain) with no increases in insulin concentration. Glucose concentrations reported by Szabo et al (2000) were similar to those measured in the current study.…”
Section: High-protein Diet Following Ovariohysterectomymentioning
confidence: 98%
“…Szabo et al (2000) reported increased blood glucose concentrations in cats following ovariohysterectomy (and weight gain) with no increases in insulin concentration. Glucose concentrations reported by Szabo et al (2000) were similar to those measured in the current study. Kanchuk et al (2003) reported increased insulin concentrations of neutered male v. intact male cats; however, changes over time within the neutered males were not statistically analyzed.…”
Section: High-protein Diet Following Ovariohysterectomymentioning
confidence: 98%
“…No caso da LHF, grande parte dos gatos que a desenvolvem são obesos e, ao sofrerem um processo patológico causador de anorexia, mobilizam ácidos graxos das reservas adiposas através de lipólise (Ettinger and Feldman, 2004). Com efeito, o substrato energético utilizado deixa de ser a glucose e passa a ser os ácidos graxos e as cetonas (Szabo et al, 2000). A excessiva acumulação de triacilgliceróis nos hepatócitos afeta a função hepática e pode culminar em morte (Hall et al, 1997).…”
Section: Pubvetunclassified
“…Em possa afetar gatos de qualquer idade, a doença surge mais comumente entre os quatro e os quinze anos. Existem vários mecanismos fisiopatológicos que estão na base do desenvolvimento da FHL: o aumento do fluxo de ácidos graxos livres para o fígado, o aumento da síntese hepática de ácidos graxos, as alterações na oxidação dos ácidos graxos no hepatócito e a diminuição do transporte pelas lipoproteínas de muito baixa densidade (Szabo et al, 2000). Brown et al (2000) propõem como causas o aumento da lipólise periférica secundária a uma deficiência absoluta ou relativa em insulina, o fígado gordo induzido por má nutrição proteicocalórica (similar ao kwashiorkor ou marasmus em humanos), a deficiência em aminoácidos essenciais (arginina e metionina) a que dá origem a uma incapacidade de sintetizar apoproteínas suficientes para mobilizar os lipídios hepáticos, a deficiência em compostos lipotróficos, a deficiência congénita ou adquirida da oxidação dos ácidos gordos e a lesão peroxissomal hepática devido a stress oxidativo.…”
Section: Introductionunclassified